Efek Kombinasi Sistem Pengaturan Air Irigasi dengan Pemangkasan Daun Bawah Terhadap Efisiensi Air dan Radiasi, Serta Produktivitas Tanaman Jagung pada Lahan Kering Beriklim Kering - Yonny Koesmaryono; . Haruna; Budi Kartiwa; . Impron (Jurnal Ilmu Pertanian Indonesia, 2012)
Study on the effect of dose management on water irrigation and the effect of pruning corn lower leaves on productivity of Lamuru variety grown on dry land of dry climate area has been done. The experiment was organized at Naibonat Experimental Station, East Kupang Subdistrict, Kupang, East Nusa Tenggara, from June to October 2011. The area used was 72 × 32 m using split plot design methods, employing two treatments. The first treatment was conducted on the main plot with water irrigation dose given 100, 80, and 60% the dose control was according to the farmer’s customary. The second treatment was applied by pruning or not pruning the lower leaves at the generative phase on the determined submain plot. The result showed that dose of water irrigation of 80 and 60% gave significant effect on corn productivity, that is 7.3 and 5.3 ton/ha, but not significant to the control (6.6 ton/ha). On the other hand, the treatment with and without leaf pruning did not give significant effect on the growth component because pruning was conducted during the generative phase. The Anova test result of corn productivity was not significantly different between the treatment of with and without pruning. The treatment of 80% dose of water irrigation could save water until 842 m3 or 20% per planting season per hectare. Meanwhile, the farmer’s customary wasted the water up to 2.105 m3 or 50% per planting season per hectare. Based on the results, the optimizing of water irrigation interval is seven times more efficient in one planting period as compared to 14 irrigation times in one planting period.